ATOMIC ABSORPTION SPECTROMETRY—A REVIEW (Journal of Forensic Medicine & Toxicology, 2011)
Atomic Absorption Spectroscopy (AAS) plays important role for analysis of several metals It’s use is readily understood from breadth of its applications. The range of material that can be analyzed by AAS is essentially unlimited. Applications are found in such diverse field as forensic science, pharmaceuticals, food and agriculture, biological and clinical chemistry, environmental chemistry and many others.It is a very common and simple instrument which is available in nearly almost all the laboratory.
Keywords: Atomic Absorption Spectroscopy; Metals; AAS; Absorption